(untitled) (Research, Society and Development, 2021)
The objective of this study is to present an overview of Inglehart’s post-materialist theory in four countries in the Southern Cone (Argentina, Brazil, Chile and Uruguay) discussing the profile of materialists and post-materialists and their changes over time. For this purpose we carried out a descriptive analysis of materialistic and post-materialistic individuals profiles according to a set of sociodemographic variables, and then we applied a binomial logistic model to verify the influence of these variables in determining each profile. We used data from the World Value Survey at three different moments in time (1990s, 2000s and 2010s). Contrary to what we expected, the results show that the differences among the profiles are not expressive although tend to corroborate the Inglehart theory. The results also contribute to understanding the relationship between the context in which an individual lives and his behaviors and values, especially in unequal realities such as Latin America.